2013
DOI: 10.7287/peerj.preprints.171v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal satisfaction about childhood immunization in primary health care center, Egypt

Abstract: Background: Childhood immunization is the most effective preventive services, and is critical to monitor and evaluate. A study reported an association between parental satisfactions with pediatric care and up-to-date immunization at 24 months independent of maternal age, race, and education. In addition to promoting utilization, satisfaction may increase involvement in the health care process. Health system factors included inconvenient clinic hours, dates or locations, waiting lines, and conflicting informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
1
1
Order By: Relevance
“…Maternal knowledge was found to be a significant factor affecting maternal satisfaction towards childhood vaccination. This is in line with findings reported from previous studies in different parts of Ethiopia [ 23 , 35 ]. This might be since knowledge is a powerful predictor of attitude and satisfaction is strongly related to one’s attitude.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Maternal knowledge was found to be a significant factor affecting maternal satisfaction towards childhood vaccination. This is in line with findings reported from previous studies in different parts of Ethiopia [ 23 , 35 ]. This might be since knowledge is a powerful predictor of attitude and satisfaction is strongly related to one’s attitude.…”
Section: Discussionsupporting
confidence: 94%
“…The finding was higher than studies conducted in Pakistan, Jimma, Jiggija, Hadiya, Egypt, Nigeria, Timor, Addis Ababa, and Bahir Dar [ 1 , 20 25 , 32 , 35 , 45 , 46 ]. But this finding is lower when compared with studies conducted in Ethiopia, Nigeria, Egypt and Saudi Arabia [ 18 , 19 , 23 , 24 , 26 , 47 ]. Not suprisingly, the difference can be associated to differences in awareness and literacy, the subjective nature of the response, and the items used to measure the satisfaction level between the studies.…”
Section: Discussioncontrasting
confidence: 57%
“…Almost similar findings were revealed in a study conducted among mothers who were attending urban primary health care center, Egypt. 13 Findings of the study revealed that education level was of Intermediate level (Primary/Secondary) in 54.6% mothers, high education (University education) was observed in 33.7% mothers, while 8.1% of mothers could read & write only and 8.1% of them were illiterate.…”
Section: Discussionmentioning
confidence: 87%